Relative efficacy of topical non-steroidal anti-inflammatory drugs and topical capsaicin in osteoarthritis: protocol for an individual patient data meta-analysis - Persson, Monica S.M.; Fu, Yu; Bhattacharya, Archan; Goh, Siew-Li; Middelkoop, Marienke van; Bierma-Zeinstra, Sita M.A.; Walsh, David A.; Doherty, Michael; Zhang, Weiya (BioMed Central, 2016)
Background